Effect of various concentrations of Minimal Essential Medium vitamins (MEM vitamins) on development of - Hamed Karami Shabankareh; Farokh Kafilzadeh; Leila Soltani (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Improvements in culture media formulations have led to an increasein the ability of sheep embryo in culture throughout the preimplantation period.Objective: This study was carried out to evaluate the effects of variousconcentrations of MEM vitamins during in vitro maturation of sheep oocytes andsubsequent embryo development.Materials and Methods: Sheep ovaries were collected from a slaughterhouse andtransported to the laboratory. Oocytes were matured in SOF medium supplementedwith, eCG, hCG and EGF in various concentrations of MEM vitamins (control, 0.5,1 and 1.5 ) for 24h. The cumulus oocyte compelex (COCs) were co-incubated withepididymal spermatozoa of post mortem rams in synthetic oviduct fluid fertilization(SOFF) medium with 10% heat inactivated estrous sheep serum for 18h. Embryoswere cultured in synthetic oviduct fluid culture 1 (SOFC1) medium for 48h followedby cultured in synthetic oviduct fluid culture 2 (SOFC2) medium for six days.Results: Addition of 0.5 and 1  MEM vitamins significantly increased (P< 0.05)overall blastocyst development (21.62% and 22.33%; respectively) compared with1.5MEM vitamins (15.59%), but there was no difference between control, 0.5 and1MEM vitamins in the percentage of embryos successfully developing to theblastocyst stage (19.50%, 21.62% and 22.33% respectively).Conclusion: It seems that addition of 1.5  of MEM vitamins has detrimental effecton blastocyst rate.